Themistius’ Paraphrase of Posterior Analytics 71a17-b8: An Example of Rearrangement of an Aristotelian Text - Achard, Martin (Laval théologique et philosophique, 2008)
AbstractThe author shows how Themistius, in his paraphrase, reorganizes the parts of Posterior Analytics 71a17-b8. Through a close analysis of Aristotle’s text, he demonstrates that this reorganization rests on a sound reading of Aristotle, and that, in all likelihood, it was prompted by external evidence that Themistius had at his disposal.